ELEMENTS OF THE IRON AND MANGANESE CYCLES IN LAKE BAIKAL - Granina L.Z.; Callender E. (My University, 2007)
Using data obtained in recent years, we considered the external mass balance and characteristics of internal iron and manganese cycles in Lake Baikal (biological uptake, remineralization, sedimentary and diffusive fluxes, accumulation in sediments, time of renewal, etc.). Some previous results and common concepts were critically reevaluated.